Joint optimization of transmission and edge offloading for energy-aware point cloud video streaming - LIU Wei; ZHU Yule; FU Chen; WANG Xi (Tongxin xuebao)
The transmission of point cloud video streaming requires the scheduling of various computing and transmission resources. Existing research rarely considers the energy consumption issues caused by the computing tasks of terminal display devices. To solve this problem, a point cloud video streaming transmission scheme assisted by mobile edge computing (MEC) was proposed, which offloaded part of computing tasks to the MEC server based on the access bandwidth and point cloud video content. A joint optimization model was established in this scheme to maximize the quality of user’s viewing experience and minimize the energy consumption of terminal device under the constraints of network resources, terminal and edge computing resources. Experimental results show that the proposed scheme can improve the viewing quality of users and reduce the energy consumption of terminal equipment compared with the contrast scheme under different conditions.